2011
DOI: 10.1186/ar3237
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies of IgG, IgA and IgM isotypes against cyclic citrullinated peptide precede the development of rheumatoid arthritis

Abstract: IntroductionWe and others have previously shown that antibodies against cyclic citrullinated proteins (anti-CCP) precede the development of rheumatoid arthritis (RA) and in a more recent study we reported that individuals who subsequently developed RA had increased concentrations of several cytokines and chemokines years before the onset of symptoms of joint disease. Here we aimed to evaluate the prevalence and predictive values of anti-CCP antibodies of IgG, IgM and IgA isotype in individuals who subsequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
3
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(163 citation statements)
references
References 15 publications
7
143
3
7
Order By: Relevance
“…This strengthens the hypothesis that smoking is of etiological importance in the very early stages of RA development [96]. Among pre-RA patients who are smokers, IgA anti-CCP antibodies appear significantly earlier than in non-smokers [97]. However, the mechanism by which cigarette smoking contributes to the development of RA is not known.…”
Section: Environmental Triggerssupporting
confidence: 76%
“…This strengthens the hypothesis that smoking is of etiological importance in the very early stages of RA development [96]. Among pre-RA patients who are smokers, IgA anti-CCP antibodies appear significantly earlier than in non-smokers [97]. However, the mechanism by which cigarette smoking contributes to the development of RA is not known.…”
Section: Environmental Triggerssupporting
confidence: 76%
“…For instance, it is well established that a combination of cigarette smoking and genetic carriage of HLA-DRB1/SE is a strong risk of developing IgG-ACPA positive, but not IgG-ACPA negative, RA (Morgan et al 2009;Padyukov et al 2011). Although derived from studies of much smaller format, there are indications of serum IgA-ACPA being even more strongly related to smoking but not to SE (Verpoort et al 2007;Svärd et al 2010) and Kokkonen et al showed that smoking pre-RA patients developed circulating IgA-CCP earlier than did their non-smoking counterparts (Kokkonen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] These ACPA responses, primarily characterized by IgG 1 and IgG 4 subtypes (99 and 98% of ACPA-positive RA patient sera, respectively), have been found to be present up to years before disease onset and to be highly specific (98%) and sensitive (up to 80%) for RA. [16][17][18][19][20][21] Thus, APCA are used as a supplement to clinical diagnosis of RA. 20 The most frequently used peptide-based immunoassay for ACPA detection is based on cyclic citrullinated peptides (CCP).…”
Section: Introductionmentioning
confidence: 99%